2015
DOI: 10.1002/app.42042
|View full text |Cite
|
Sign up to set email alerts
|

Fouling control on microfiltration/ultrafiltration membranes: Effects of morphology, hydrophilicity, and charge

Abstract: Membrane‐based separation processes are very susceptible to flux decline because of concentration polarization and fouling problems. Despite the immense applications of low‐pressure driven microfiltration (MF) and ultrafiltration (UF) membranes in various fields, fouling is considered a major negative aspect, and it renders the membrane with a reduced lifetime. The important membrane properties, hydrophilicity, charge, and morphology mainly gained by the membrane during its formation process are considered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(107 citation statements)
references
References 173 publications
4
99
0
Order By: Relevance
“…Fouling is affected by hydrodynamic conditions, membrane properties, and feed solution properties. A dependence of fouling on membrane surface roughness has been experimentally and theoretically observed . These studies focused on randomly rough surfaces, but recent research has found a correlation between fouling resistance and induced regular surface roughness .…”
Section: Introductionmentioning
confidence: 99%
“…Fouling is affected by hydrodynamic conditions, membrane properties, and feed solution properties. A dependence of fouling on membrane surface roughness has been experimentally and theoretically observed . These studies focused on randomly rough surfaces, but recent research has found a correlation between fouling resistance and induced regular surface roughness .…”
Section: Introductionmentioning
confidence: 99%
“…This deposition, also termed membrane fouling, causes a decrease in the water flux that subsequently requires an increase in the frequency of back washing and membrane maintenance. This combination limits the lifetime of the membranes and reduces the cost efficiency . Membrane fouling can be reduced through modifications to the membrane, such as adding hydrophilic polymers …”
Section: Introductionmentioning
confidence: 99%
“…In general, to enhance the membrane antifouling property, the surface modification is potentially the most sustainable solution. The idea is to introduce hydrophilic groups with suitable charged functionality onto membrane surface . Recently, various strategies have been proposed in the development of fouling resistance of the TFC‐PA membranes, particularly through either surface coating or grafting of hydrophilic, brush‐like or hyperbranched, hydrogels, or zwitterionic polymers.…”
Section: Introductionmentioning
confidence: 99%